Stem cell injections for osteoarthritis of the knee - Whittle, Samuel L (Cochrane Database Syst Rev, 2019)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the benefits and harms of stem cell injections for people with osteoarthritis of the knee, in terms of pain, function, disease progression, quality of life, and adverse events.